The Influence of Digital Innovation and Reputation on Buyer-Supplier Relationship Mediated by Supply Chain Flexibility - Evensius, Petrus; Riza, Fahrul (Journal of World Science, 2024)
This research aims to determine and analyze the influence of digital innovation and reputation on the buyer-supplier relationship mediated by supply chain flexibility. Empirical study: PT vendors. Astra Daihatsu Motor. The method used in this research is quantitative research. The population in this research is the buyer-supplier of the Automotive Manufacturing Company Vendor PT. Astra Daihatsu Motor. The sample required for this research is around 222 respondents from 500 employees. So, the research results show that digital innovation positively impacts buyer-supplier relationships and supply chain flexibility. Likewise, company reputation also has a positive influence on these two variables. In addition, the results of the analysis show that supply chain flexibility mediates the relationship between digital innovation/reputation and buyer-supplier relationships. The practical implication of this research is the importance of investing in digital innovation and maintaining a company's reputation to strengthen business relationships and increase flexibility in dealing with changing markets and customer needs. This research provides insight for managers in managing supplier relationships, improving their supply chain performance through technology, and building a strong reputation.